CLASSROOM INTERACTION IN TEACHING ENGLISH AS A SECOND LANGUAGE - Aliyeva Dilafruz Mukhtarovna (Galaxy International Interdisciplinary Research Journal, 2023)
This article describes the modern pedagogical technologies used in the education system. In education system all modern pedagogical techniques and types of methods are considered in this article. In addition to exposure, students perform better when they have motivation to communicate.